Comparative biomechanical analysis of 110 m hurdles of Igor Kovac and Peter Nedelicky - Kampmiller, T.; Slamka, M.; Vanderka, M. (Kinesiologia Slovenica, 1999)
The biomechanical characteristics of two athletes` technique in 100m hurdles were analysed, trying to find the parameters leading to the difference in their running results. The measurements were performed in the final race of the IAAF-II meeting Slovnaft `97 in Bratislava. The subjects were I.K. with a personal best of 13.13 s and P.N. with 13.97 s. They were filmed with a S-VHS camera at 50 Hz on the 8th hurdle. The film was analysed with the BAF 2D video analysis system, the time, space and velocity parameters were obtained and joint moments of the knees and hips computed. The competitors realise the support phase before and after the hurdle in different ways. The position of C.G. before the hurdle is lower for I.K., he has a longer breaking and acceleration phase. However, differences are mostly in the kinematics after the hurdle. I.K. goes to touch-down with a higher C.G. position. His elastic stiffness is more developed because of quicker deceleration of C.G. lowering during the first part of the support phase after the hurdle. Also, during take-off, the position of C.G. of I.K. is higher. This leads to I.K.`s higher velocity with shorter support and acceleration phases.